Public Goods and the Technology of Consumption - Sandmo, A. (Review of Economic Studies, 1973)
Journal Article Public Goods and the Technology of Consumption Get access Agnar Sandmo Agnar Sandmo Norwegian School of Economics and Business Administration, Bergen Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 4, October 1973, Pages 517–528, https://doi.org/10.2307/2296585 Published: 01 October 1973